Активированное спекание вольфрама - Матренин С. В. Сергей Вениаминович; Ильин А. П. Александр Петрович; Слосман А. И. Аркадий Иосифович; Толбанова Л. О. Людмила Олеговна (Физика, 2008)
Заглавие с титульного листа